2015
DOI: 10.1016/j.jfma.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the GOLD 2013 classification in predicting exacerbations and mortality in Taiwanese patients with chronic obstructive pulmonary disease

Abstract: The GOLD 2013 classification has powerful ability to predict exacerbation, but poor ability to predict mortality. The prognostic validity of the GOLD 2013 classification to predict exacerbations was better than the GOLD 2007 classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“… 14 In addition, several studies have shown that the ABCD classification is not a better predictor of mortality than spirometric grades. 8 , 15 17 In the present study, although a statistically significant difference was observed across the ABCD groups and the spirometric grades for the GOLD 2017 classification, it did not perform well with regard to predicting mortality. The GOLD guidelines for COPD diagnosis and management do not address clinical phenotypes and comorbidities.…”
Section: Discussioncontrasting
confidence: 85%
“… 14 In addition, several studies have shown that the ABCD classification is not a better predictor of mortality than spirometric grades. 8 , 15 17 In the present study, although a statistically significant difference was observed across the ABCD groups and the spirometric grades for the GOLD 2017 classification, it did not perform well with regard to predicting mortality. The GOLD guidelines for COPD diagnosis and management do not address clinical phenotypes and comorbidities.…”
Section: Discussioncontrasting
confidence: 85%
“…4 Studies have compared the discrimination abilities of the GOLD 2007 and GOLD 2011 classifications to predict exacerbation and mortality. [4][5][6][7][8] Johannessen et al 5 found that the GOLD 2007 and GOLD 2011 classifications predicted respiratory hospitalization similarly well; however, Lange et al 6 and Chen et al 7 found that the GOLD 2011 classification was better than the GOLD 2007. In a pooled analysis of 22 cohorts, the GOLD 2007 and GOLD 2011 classifications did not differ significantly in predicting mortality.…”
Section: Introductionmentioning
confidence: 99%
“…They are composed of two dimensions, the COPD assessment test (CAT) and the modified Medical Research Council (mMRC) dyspnoea score for presenting symptom evaluation, lung function (GOLD stage classification) and exacerbation frequency for future risk evaluation. A series of validation studies has been conducted in different region, and showed some similar results, such as a relatively low number of category C patients, significant heterogeneity in prospective exacerbation rates in category D, no differences in the predictive value of mortality for GOLD 2011 and GOLD 2007, and a better predictive value of exacerbation for GOLD 2011 and GOLD 2007 [18]. KOBLIZEK et al [4] also compared Spanish phenotypes with GOLD categories (2011 version) and showed that the majority of frequent exacerbators were in category D regardless of the coexistence of chronic bronchitis, whereas 39% of non-exacerbators and 56% of those with ACOS were also in category D, indicating marked heterogeneity in this category.…”
mentioning
confidence: 81%